The relationship between the timing of take-off and flight length by using two different types of jump-dolls - Sasaki, T.; Tsunoda, K.; Hoshino, M.; Miyake, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study is to detect the optimal timing of jump action in ski jumping. Assuming a jumper could always produce same motions, the timing of jump action would be the most important variable for the flight distance. In this study, the jump of the two different jump-dolls were observed on the hill model (1/100). Dolls always produce same power during jump action. Thus, the flight distance solely depends on the timing of initiating the action. Therefore, it is possible to clarify the relationship between the timing and the flight distance. Methodology: Two different types of jump-dolls were developed. First doll was used two springs for producing softer power. Four springs were set in respective joints (knees and hips) of the second types of the doll. The jump doll can reproduce the same hopping action on the take-off platform. The critical point (K) in the model of jumping hill is 160 cm. The dolls are able to jump on this model hill. The position of start on in-run is 150 cm away from the edge of platform. The peg, which releases the strength of the jump doll, was put on six places every 4 cm away from the edge of platform. Five times trials in two jump dolls were executed for every peg point. All the jump actions were recorded by the NAC video camera with 500 fps. Results: The elapsed time for jump actions from squat position to full extension and speed of take-off were almost the same in both types. Using the same release point, the maximum flight distance was occurred in each doll. The release point is 4 cm before the edge of platform. The flight distance is 125 cm in type 1, and 166 cm in type 2. On the other hand, the minimum flight distance was observed in initiating jump action at the 12 cm before the edge. The flight distance is 88 cm in type 1, and 128 cm in type 2. Discussion: Smooth action on each joint is achieved by a bearing devices, although the doll is made by wood, The doll-model produces the same strength at take-off actions, because, it is possible to take the same squat position anytime. Therefore, the jump -doll can be used in the experiment of ski-jump. In this study, the difference in the flight distance is only attributed by the difference of the timing of the jump action. As an evidence of the transition of the power, the oscillation of skis was exactly observed during the initial flight phase. This phenomenon already pointed out even in the human action (Sasaki et al., 2005). In the flight distance, the most effective timing for beginning the action is clarified in this experiment by the jump-doll. Conclusion: Until the 4 cm from the edge of platform, the later the timing of beginning the action is, the larger the flight distance is. The jump-doll always transmits almost same power.